Enhancing Firm Value through CSR Disclosure in Crisis Period: Evidence from high-profile Asia-pacific firms - Atik Ul Mussanadah (Widya Dharma Journal of Business - WIJoB, 2024)
This study investigates the impact of firms’ disclosure about their CSR efforts (CSRD) on firm value during crisis periods, focusing on high-profile companies in the Asia-Pacific region. The analysis examines high-profile companies within the Asia-Pacific region during 2020-2021, using archival data sourced from the Thomson Reuters database. This study finds that CSRD significantly impacts firm value during crises. During times of crisis, transparency in CSR activities is especially valued, as stakeholders seek companies with continuous principles and ethical practices that bond as a commitment to firms’ social responsibility within their surrounding business environment. This positive reputation helps high-profile companies maintain stakeholder relationships and bolster their market standing during global challenges. It highlights CSRD as a critical strategy for enhancing firm value in crisis periods, underscoring the foundational needs of firms in fulfilling their transparency and responsibility to stakeholder trust and supporting a company’s resilience during global crises.